Akuntabilitas Pengelolaan Keuangan Desa: Studi Kasus Gampong Harapan, Kota Lhokseumawe - Mustazir Ramli (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
The objective of research is to understand about mechanisms and disign of accountability of financial management of villages and describes about the capacity of the government in the village of village financial management responsibilities. The design used is a case study with the object of research is Gampong Harapan Kota Lhokseumawe. Data collection techniques such as observation, interviews and documentation for later analysis using interactive data analysis methods, further to assure the validity of data used triangulation techniques.